INTELLECTUAL PROPERTY PROTECTION FOR BRAZILIAN SOFTWARE DEVELOPMENT COMPANIES IN THE PROCESS OF INTERNATIONALIZATION - Silva, Tainá de Melo Soares; Ribeiro, Luana da Silva; Nascimento, Julio Cesar (Seven Editora, 2026)
This study aims to analyze the main strategies for the protection of intellectual property (IP) adopted by Brazilian software development companies in their process of internationalization. Expanding into foreign markets brings complex challenges, especially regarding the protection of intangible assets, such as patents, trademarks, and copyrights. The research proposes an in-depth investigation into the effectiveness of legal measures, focusing on IP registration with the Instituto Nacional da Propriedade Industrial (INPI) and the adequacy of companies to international legislation, as well as an analysis concerning national disputes over intellectual property, with an empirical focus on the state of São Paulo. Furthermore, the study will conduct a market analysis using data from public databases and sectoral reports, aiming to identify the trends and obstacles faced by Brazilian companies during their internationalization. Finally, the research will provide evidence-based recommendations that can assist companies in developing more effective IP protection strategies aligned with global challenges, aiming at greater competitiveness and legal security in the international scenario.DOI: https://doi.org/10.56238/sevened2026.001-025